2012
DOI: 10.1007/s10457-012-9562-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological response of Vitex negundo var. heterophylla and Ziziphus jujuba var. spinosa to the combined impact of drought and shade

Abstract: Light and soil moisture availability are two important abiotic factors influencing plant growth in an agroforestry system. Different soil moisture and light treatments were applied to examine the combined impact of drought and shade on the morphological plasticity of Vitex negundo var. heterophylla (Chinese chastetree) and Ziziphus jujuba var. spinosa (Spine jujube). We found that the interaction of light and soil moisture was orthogonal in the two species. V. negundo captured irradiance efficiently with relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…Reduced SLA under high light suggested that the lower vapor-pressure deficit under shade compensated for high transpiration load from high SLA and drought (Quero et al 2006;Du et al 2013). Therefore, these results did not support predictions of the trade-off hypothesis that shade stress aggravated drought-induced damages (Smith and Huston 1989).…”
Section: Which Hypothesis To Support?mentioning
confidence: 84%
See 2 more Smart Citations
“…Reduced SLA under high light suggested that the lower vapor-pressure deficit under shade compensated for high transpiration load from high SLA and drought (Quero et al 2006;Du et al 2013). Therefore, these results did not support predictions of the trade-off hypothesis that shade stress aggravated drought-induced damages (Smith and Huston 1989).…”
Section: Which Hypothesis To Support?mentioning
confidence: 84%
“…The watering regimes severed as severe, moderate, mild water deficit and well water conditions, respectively. The 10% sunlight was selected to simulate the irradiance of forest understory after measuring the irradiance of forest understory in local areas (Du et al 2013), and the 66% sunlight equaled to irradiance of forest gaps, which served as control here. Ten seedlings were used as replication in each water and light treatment combination.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic mechanism may be restricted when natural plant populations endure some discrete human‐caused disturbance, such as heavy metal pollution (Kim et al., ), experimental disturbance (Herrera & Bazaga, ), and oil spills (Robertson et al., ). According to our field investigations and planting experiments (Du et al., ), Chinese chastetree tends to distribute in open habitats with plentiful light. Understory individuals might sometimes undergo aboveground dieback due to shade and drought, but individuals in open habitat were disturbed by human‐caused cutting in five (Fanggan, Liantaishan, Mengshan, Menglianggu, and Taishan) of seven study sites (see Figure a).…”
Section: Discussionmentioning
confidence: 95%
“…Chinese chastetree in roadside and bush habitats is frequently cut by farmers as firewood or to prevent it from occupying farmlands. It can adapt to cardinal environmental factors through modification of a series of morphological and physiological characteristics (Du, Guo, Zhang, & Wang, 2010;Du et al, 2012). As a long long-lived perennial, V. negundo var.…”
mentioning
confidence: 99%